2006
DOI: 10.1039/b504014k
|View full text |Cite
|
Sign up to set email alerts
|

Natural products from medicinal plants: non-alkaloidal natural constituents of the Thalictrum species

Abstract: Thalictrum is an important plant genus that is widely used in traditional medicine. In this review considerable attention has been given to triterpenoid saponins in connection with their specific distribution in the Thalictrum genus and with their biological activity. All other non-alkaloid compounds isolated from the Thalictrum genus are also reviewed; these metabolites are discussed in relation to their structural features and to their role in the plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…The DPPH free radical scavenging activity was concentration dependent and TF extracts with higher phenol content scavenged free radicals more effectively. Earlier studies have reported the presence of protocatechuic acid, caffeic acid, and p-coumaric acids in Thalictrum [45] .The TF extracts from Kedarkantha (3086 m) and Sankri (2031 m) showed significantly higher free radical scavenging activity as compared to TF extracts from a lower altitude. In all the models tested, the antioxidant activity of berberine was studied in relation to that of ascorbic acid, a known standard potent antioxidant.…”
Section: Discussionmentioning
confidence: 80%
“…The DPPH free radical scavenging activity was concentration dependent and TF extracts with higher phenol content scavenged free radicals more effectively. Earlier studies have reported the presence of protocatechuic acid, caffeic acid, and p-coumaric acids in Thalictrum [45] .The TF extracts from Kedarkantha (3086 m) and Sankri (2031 m) showed significantly higher free radical scavenging activity as compared to TF extracts from a lower altitude. In all the models tested, the antioxidant activity of berberine was studied in relation to that of ascorbic acid, a known standard potent antioxidant.…”
Section: Discussionmentioning
confidence: 80%
“…Myricetin, a nontoxic dietary flavonoid, could be easily found in many natural foods and medicinal herbs [26,27]. Reports indicate that myricetin does not cause tumor formation in mice and attenuates the number of diol-epoxide-induced pulmonary tumors per mouse [28].…”
Section: Discussionmentioning
confidence: 99%
“…Certain species of Thalictrum are economically significant in the pharmacological [4] and horticultural industries [38]. The development of this technique will facilitate the study of gene function of clinically relevant secondary metabolite biosynthesis in Thalictrum .…”
Section: Discussionmentioning
confidence: 99%
“…The genus exhibits a range of floral morphologies including four breeding systems and two pollination syndromes [2]. Commonly known as “meadow rues”, these perennial woodland herbs have been actively studied for the medicinal value of their secondary metabolites [3], [4], [5]. This lineage is ideally suited for the study of the origins of core eudicot diversity because of: (1) Its basal phylogenetic position within the eudicots and (2) The presence of ancestral floral traits, such as free, uniovulate carpels with ascidiate (open) development and variable number of spirally arranged floral organs [6].…”
Section: Introductionmentioning
confidence: 99%